Fiqh Muamalah Analysis of the Government Digital Procurement System - Choirul Amirudin (Journal of Islamic Digital Economic and Finance, 2025)
Introduction: Presidential Regulation No. 46 of 2025 concerning the Procurement of Goods/Services which has three important stages, namely preparation, selection and implementation. The implementation of e-procurement is a form of public administration modernization that aims to improve efficiency, transparency, and accountability in the management of the state budget. Objective: This study aims to analyze the perspective of fiqh muamalah on the implementation of the government's digital procurement system (e-procurement) in Indonesia. This research will also identify potential violations of Sharia principles in the digital procurement system and provide recommendations for system improvements to better align with Islamic values. Method: Using qualitative methods and secondary data sources, this study examines the compatibility of sharia principles in the government's technology-based procurement system for goods and services. Result: The conclusion shows that first, in general, Presidential Regulation No. 46 of 2025 concerning the Procurement of Government Goods/Services must start with good planning, the selection of good alternatives and the need to use the best procurement strategy. The government's digital procurement system can be in line with the principles of fiqh muamalah if it meets the requirements of a valid contract, transparency, fairness, and avoids elements that are prohibited in Islam such as gharar, riba, and tadlis. Implication: This study contributes new insights to the contemporary fiqh muamalah discourse regarding the adaptation of Islamic law to technological developments in the public sector.